2019
DOI: 10.1038/s41598-019-44256-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting chitosan and gold nanoparticles for antimycobacterial activity of in silico identified antimicrobial motif of human neutrophil peptide-1

Abstract: The upsurge of drug resistant tuberculosis is major health threat globally. To counteract, antimicrobial peptides are being explored as possible alternatives. However, certain limitations of peptide-based drugs such as potential toxicity, high cost and relatively low stability need to be addressed to enhance their clinical applicability. Use of computer predicted short active motifs of AMPs along with nanotechnology could not only overcome the limitations of AMPs but also potentiate their antimicrobial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…Utilizing chitosan as the nanogel matrix often provides a positive surface charge, which may increase macrophage uptake, making it a suitable delivery system for treatment of intracellular infections, such as M. tuberculosis. Sharma et al showed that encapsulation of the peptide pep-H in chitosan nanogels resulted in the formation of nanoparticles with a cationic surface charge, which then allowed an 80% reduction of intracellular bacterial load in comparison to equivalent concentrations of peptide in solution, which only showed a 12% reduction in intracellular M. tuberculosis load [125]. Chitosan-based nanogels have also demonstrated an increased residence and a close contact with mucosa due to their mucoadhesive property, making them a desirable system for topical mucosal administration [126].…”
Section: Natural Cationic Polymer-based Nanogelsmentioning
confidence: 99%
“…Utilizing chitosan as the nanogel matrix often provides a positive surface charge, which may increase macrophage uptake, making it a suitable delivery system for treatment of intracellular infections, such as M. tuberculosis. Sharma et al showed that encapsulation of the peptide pep-H in chitosan nanogels resulted in the formation of nanoparticles with a cationic surface charge, which then allowed an 80% reduction of intracellular bacterial load in comparison to equivalent concentrations of peptide in solution, which only showed a 12% reduction in intracellular M. tuberculosis load [125]. Chitosan-based nanogels have also demonstrated an increased residence and a close contact with mucosa due to their mucoadhesive property, making them a desirable system for topical mucosal administration [126].…”
Section: Natural Cationic Polymer-based Nanogelsmentioning
confidence: 99%
“…Recently, a 15-amino acid long fragment of HNP1, Pep-H, was tested in vitro against Mtb H37Rv, displaying an inhibitory activity of 60% and 92% at 5 μg/mL and 10 μg/mL, respectively, the latter being taken as its MIC ( Table 1 ). The peptide was also tested against intramacrophagic Mtb , demonstrating a 91% reduction of intracellular mycobacterial growth at 5 μg/mL [ 75 ]. Moreover, Pep-H not only led to a significant increase in the levels of RNOS and IFN-γ but also decreases pro-inflammatory cytokines such as TNF-α, IL-6 and MCP-1, highlighting immunomodulatory properties in addition to direct antimicrobial activity against Mtb [ 75 ].…”
Section: Animal Amp With Anti-tubercular Activitymentioning
confidence: 99%
“…The fabrication process of GMNPs used a "one pot" polyol synthesis method, which is a modified version of the high temperature hydrolysis process that was developed previously [34,35]. Basically, four different solutions were prepared before the GMNP synthesis process.…”
Section: Fabrication Of Gold Magnetic Nanoparticles (Gmnps)mentioning
confidence: 99%